2021
DOI: 10.3390/ijms22010423
|View full text |Cite
|
Sign up to set email alerts
|

The p24 Complex Contributes to Specify Arf1 for COPI Coat Selection

Abstract: Golgi trafficking depends on the small GTPase Arf1 which, upon activation, drives the assembly of different coats onto budding vesicles. Two related types of guanine nucleotide exchange factors (GEFs) activate Arf1 at different Golgi sites. In yeast, Gea1 in the cis-Golgi and Gea2 in the medial-Golgi activate Arf1 to form COPI-­coated vesicles for retrograde cargo sorting, whereas Sec7 generates clathrin/adaptor­-coated vesicles at the trans-Golgi network (TGN) for forward cargo transport. A central question i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Arf1 drives the assembly of different coats onto budding vesicles, which are closely connected with the Golgi apparatus. [42] Similarly, our data indicated that Arf1 was associated with several vesicle transport-related proteins, and Arf1 affected the localization and expression of cis-Golgi marker GM130 and GTPase Rab35. Indeed, the dominantnegative Arf1 mutant in myotubes alters the subcellular distribution of GM130, which impairs endoplasmic reticulum-Golgi traffic.…”
Section: Discussionsupporting
confidence: 67%
“…Arf1 drives the assembly of different coats onto budding vesicles, which are closely connected with the Golgi apparatus. [42] Similarly, our data indicated that Arf1 was associated with several vesicle transport-related proteins, and Arf1 affected the localization and expression of cis-Golgi marker GM130 and GTPase Rab35. Indeed, the dominantnegative Arf1 mutant in myotubes alters the subcellular distribution of GM130, which impairs endoplasmic reticulum-Golgi traffic.…”
Section: Discussionsupporting
confidence: 67%